Adsorption of cationic dyes using Sargassum horneri and Ulva australis biosorbent - Narae Kim; Jae-Wook Lee; Taesoon Jang; Soyeong Yoon; Jin-Hyuk Choi; Eunmi Hong; Jeong-Ann Park (Desalination and Water Treatment, 2025)
Marine algae, Sargassum horneri (S. horneri) and Ulva australis (U. australis), massively occur along the coasts of South Korea and are harvested annually due to negative impact on marine environment. To convert this biowaste into a biosorbent, this study investigated the adsorption capacity of cationic dyes (methylene blue (MB) and toluidine blue (TB)) from aqueous solutions. The collected algae were washed with tap and distilled water, dried at 80 °C, ground, and sieved to obtain a uniform biosorbent (average size of 0.4 mm). Adsorption parameters, including reaction time, initial dye concentration, and temperature were investigated. Kinetic experiments revealed that dye adsorption by both biosorbents reached equilibrium within 2 h, following a pseudo-second-order kinetic model. Langmuir equation described well of the adsorption behavior of both dyes, demonstrated monolayer adsorption. Adsorption of MB and TB were more effective using S. horneri than U. australis. Furthermore, as the temperature increased, the Gibbs free energy change (∆G°) decreased, confirming spontaneous and endothermic reaction. Also, both biosorbents successfully reused 3 times after simple regeneration process (treated in 0.1 M HCl solution for 4 h). These findings highlight the potential of S. horneri and U. australis biosorbent as effective natural adsorbents for cationic organic dye removal.